Diseño del sistema de suministro eléctrico de la empresa ELECTRONICAGOIA S.A. Aplicando parámetros de calidad de energía. - Sánchez Mamarandi, Darwin David (2020)
In the ELECTRONICAGOIA company will be carried out the design of the power supply system applying energy quality parameters. All of these parameters can determine whether the electrical energy is adequate to ensure that an equipment or the entire system is functioning properly, without suffering alterations and damage to its operation, allowing for better performance and control in its production processes. For this reason, the design of the industry's power supply system aims to distribute the electric energy optimally, with minimal fluctuations in voltage and current in sensitive equipment of all the production sectors of the industry, as well as ensuring proper load selection and coordination of the protections, so that the system is protected in any event of failure that could appear in the electrical installation; also reduce disturbances affecting electrical and electronic equipment, by developing grounding systems, which take care of the life of the equipment in addition to the integrity of the personnel, this contributing to the company having a safe, reliable and efficient electrical system. A correct design of the power supply system ensures that the electrical energy is used correctly in each work and production area, which is fundamental to the development of the ELECTRONICAGOIA S.A. Company, as it will represent a technical and economic savings concerning faults or damaged machinery.